Preclinical Studies on Intestinal Administration of Antisense Oligonucleotides as a Model for Oral Delivery for Treatment of Duchenne Muscular Dystrophy - Maaike van Putten; Courtney Young; Sjoerd van den Berg; Amanda Pronk; Margriet Hulsker; Tatyana G Karnaoukh; Rick Vermue; Ko Willems van Dijk; Sjef de Kimpe; Annemieke Aartsma-Rus (Elsevier, 2014)
Antisense oligonucleotides (AONs) used to reframe dystrophin mRNA transcripts for Duchenne muscular dystrophy (DMD) patients are tested in clinical trials. Here, AONs are administered subcutaneously and intravenously, while the less invasive oral route would be preferred. Oral delivery of encapsulated AONs supplemented with a permeation enhancer, sodium caprate, has been successfully used to target tumor necrosis factor (TNF)-α expression in liver. To test the feasibility of orally delivered AONs for DMD, we applied 2'-O-methyl phosphorothioate AONs (with or without sodium caprate supplementation) directly to the intestine of mdx mice and compared pharmacokinetics and -dynamics with intravenous, intraperitoneal, and subcutaneous delivery. Intestinally infused AONs were taken up, but resulted in lower plasma levels compared to other delivery routes, although bioavailability could be largely improved by supplementation of sodium caprate. After intestinal infusion, AON levels in all tissues were lower than for other administration routes, as were the ratios of target versus nontarget organ levels, except for diaphragm and heart where comparable levels and ratios were observed. For each administration route, low levels of exon skipping in triceps was observed 3 hours post-AON administration. These data suggest that oral administration of naked 2'-O-methyl phosphorothioate AONs may be feasible, but only when high AON concentrations are used in combination with sodium caprate.